Effects of polarized training vs. other training intensity distribution models on physiological variables and endurance performance in different-level endurance athletes: a scoping review - Rivera-Köfler, T.; Varela-Sanz, A.; Padrón-Cabo, A.; Giráldez-García, M. A.; Muñoz-Pérez, I. (The Journal of Strength and Conditioning Research, 2025)
This scoping review aimed to analyze the long-term effects of polarized training (POL) on key endurance physiological- and performance-related variables and to systematically compare them with other training intensity distribution (TID) models in endurance athletes of different performance levels. Four TID models were analyzed: POL, pyramidal (PYR), threshold (THR), and block (BT) training models. The literature search was performed using PubMed, SportDiscus, Scopus, and Web of Science databases. Studies were selected if they met the following criteria: compared POL with any other TID model, included healthy endurance athletes, men, and/or women; reported enough information regarding the volume distribution in the different training intensity zones (i.e., zone 1, zone 2, and zone 3), assessed physiological (i.e., maximum/peak oxygen uptake, speed or power at aerobic and anaerobic thresholds, economy of movement), and performance in competition or time-trial variables. Of the 620 studies identified, 15 met the eligibility criteria and were included in this review. According to scientific evidence, POL and PYR models reported greater maximum oxygen uptake enhancements. Both POL and PYR models improved the speed or power associated with the aerobic threshold. By contrast, all TID models effectively improved the speed or power associated with the anaerobic threshold. Further research is needed to establish the effects of TID models on the economy of movement. All TID models were effective in enhancing competitive endurance performance, but testing protocols were quite heterogeneous. The POL and PYR models seem to be more effective in elite and world-class athletes, whereas there were no differences between TID models in lower-level athletes.